Gravitomagnetic moments of the fundamental fields - Aldrovandi, R. [UNESP]; De Andrade, V. C. [UNESP]; Pereira, J. G. [UNESP] (World Scientific Publishing, 2000)
The quadratic form of the Dirac equation in a Riemann space-time yields a gravitational gyromagnetic ratio κ(S) = 2 for the interaction of a Dirac spinor with curvature. A gravitational gyromagnetic ratio κ(S) = 1 is also found for the interaction of a vector field with curvature. It is shown that the Dirac equation in a curved background can be obtained as the square-root of the corresponding vector field equation only if the gravitational gyromagnetic ratios are properly taken into account.
Keywords: acceleration; electric current; electromagnetic field; gravity; mathematics; theory